In vivo dynamics of the internal fibrous structure in smooth adhesive pads of insects - DIRKS, JAN-HENNING (My University, 2012)
Many insects with smooth adhesive pads can rapidly enlarge their contact area by centripetal pulls on the legs, allowing them to cope with sudden mechanical perturbations such as gusts of wind or raindrops. The short time scale of this reaction excludes any neuromuscular control; it is thus more likely to be caused by mechanical properties of the pad?s specialised cuticle. This soft cuticle contains numerous branched fibrils oriented almost perpendicularly to the surface. Assuming a fixed volume of the water-filled cuticle, we hypothesized that pulls could decrease the fibril angle, thereby helping the contact area to expand laterally and longitudinally. Three-dimensional fluorescence microscopy on the cuticle of smooth stick insect pads confirmed that pulls significantly decreased the fibril angle. The fibril angle variation appeared insufficient to explain the observed increase in contact area. Direct strain measurements in the contact zone demonstrate that pulls not only expand the cuticle laterally (indicating a negative Poisson?s ratio of the pad?s cuticle), but also add new contact area at the pad?s perimeter.
PUBLISHED
Keywords: Bioengineering; Biomechanics; Insect adhesion; Insect cuticle; biomaterials; Poisson's ratio